Research on transient hydraulic characteristics of the whole process of reactor coolant pump under shaft stuck accident - Qichao Xia; Xiuli Wang; Yuanyuan Zhao; Rongsheng Zhu; Zhichen Wang; Shenpeng Yang; Wei Xu (Nuclear Engineering and Technology)
In order to explore the transient hydraulic characteristics of reactor coolant pump (RCP) under shaft stuck accident (SSA), it takes CAP1400 RCP as the research object. The applicability of three turbulence simulation methods and the different accident conditions are analyzed by numerical simulations and experiments. Combined with the appropriate turbulence simulation method and significant SSA conditions, the transient hydraulic characteristics of the whole process are studied. The results show that the numerical simulations align well with experiments during the SSA transition process, with deviations mainly concentrate in the early-middle stage. Large Eddy Simulation (LES) performs well in terms of external characteristics, with the maximum deviations below 10 %. The shorter stuck shaft transition time implies more severe accident damage, with greater the parameters decrease, more drastic specific pressure energy change. Under the kz1 and kz2 conditions, the head and torque decrease first fast and then slow down, while they decrease slowly in the early stage, then decrease sharply, reaching −92.2 % and −75.6 % of the rated value when the impeller stops under the kz3 condition. In the whole process, the head and torque decrease first and then increase, while the vorticity and specific pressure energy increase first and then decrease, all of which change dramatically in the transition process and stabilize in the subsequent response stage. The results provide theoretical and technical guidance for the optimization and improvement, enhancing the capability of accident prevention and mitigation.